2015
DOI: 10.1183/09031936.00153214
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle function, dynamic hyperinflation and exertional dyspnoea in pulmonary arterial hypertension

Abstract: Despite a preserved forced expiratory volume in 1 s (FEV1)/vital capacity (VC), patients with idiopathic or heritable pulmonary arterial hypertension (PAH) may dynamically decrease their inspiratory capacity (IC) during cycle exercise (i.e. dynamic hyperinflation) [1][2][3] and this could increase exertional dyspnoea [1,3,4]. Little information is currently available about whether the reduced IC during cycle exercise is related to respiratory mechanics abnormalities or to impaired inspiratory muscle function (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 16 publications
1
51
0
Order By: Relevance
“…It is not entirely clear what drives dyspnoea, with one study showing that Borg dyspnoea ratings were higher at lower absolute levels of ventilation than in healthy subjects [29]. This same study demonstrated, however, that 60% of patients with PAH had reduced expiratory flows at low lung volumes and that dynamic hyperinflation accounted for 50-60% of the variance of Borg dyspnoea ratings during cycle ergometry [29].…”
Section: Respiratory Response To Exercise In Pahmentioning
confidence: 98%
See 2 more Smart Citations
“…It is not entirely clear what drives dyspnoea, with one study showing that Borg dyspnoea ratings were higher at lower absolute levels of ventilation than in healthy subjects [29]. This same study demonstrated, however, that 60% of patients with PAH had reduced expiratory flows at low lung volumes and that dynamic hyperinflation accounted for 50-60% of the variance of Borg dyspnoea ratings during cycle ergometry [29].…”
Section: Respiratory Response To Exercise In Pahmentioning
confidence: 98%
“…Unlike muscles, which may increase in strength/endurance with increased loading, there is mixed evidence of respiratory muscle weakness in pulmonary hypertension [12,29,31,32]. Although this does not lead to exercise limitation, it is conceivable, although unproven, that this may contribute to the sensation of dyspnoea.…”
Section: Respiratory Response To Exercise In Pahmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study directly assessed central chemoreceptor sensitivity and demonstrates its increase in PAH as well. Dyspnea is traditionally associated with ventilatory abnormalities, characterized by higher ventilatory demand, dynamic hyperinflation, and a rapid, shallow breath frequency, especially in patients with severe PAH . When compared with HF, patients with PAH have similar exercise intolerance, but are more dyspneic in relation to reduced ventilatory efficiency .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, patients with pulmonary hypertension, i.e. damage of the pulmonary vasculature, have decreased inspiratory capacity and increased dyspnoea on effort despite normal lung function [18].…”
Section: @Erspublicationsmentioning
confidence: 99%